Pengaruh Strategi Bisnis dalam Meningkatkan Sistem Pengendalian Manajemen pada Perbankan Syariah - Astria Kurniawati (Universitas Prof.Hazairin,SH Bengkulu, 2021)
The development of Islamic banking is a milestone in the success of the Islamic economy in Indonesia. Every company is vying to win the existing business competition. Islamic banking is required to have a strategy so that its products can be used by consumers. Management in Islamic banking is expected to be able to market, raise funds, channel funds, and win the current market competition. By increasing Indonesia's economic growth, Islamic banking competes with other banks to be the best in providing satisfaction and controlling its customers. A management control system is needed for the activities of an organization to achieve its goals. This writing uses the library method or collects reading material from the contents of the article which aims to collect scientific data and information, in the form of theories, books, and journals that become solutions and the basis of argumentation.